Respuesta :
Answer:
[tex]x=\frac{9+/-\sqrt{(-9)^2-4\,(1)\,(-20)} }{2\,(1)}[/tex]
Step-by-step explanation:
Recall that the quadratic formula gives you the pattern to follow in order to find the solutions to a quadratic equation of the form: [tex]ax^2+bx+c=0[/tex]
It tells us that we need to use the parameters [tex]a,\, b,[/tex] and [tex]c[/tex] in the following formula in order to get the answers for the x-values that solve it:
[tex]x=\frac{-b+/-\sqrt{b^2-4\,a\,c} }{2\,a}[/tex]
so, in our case, [tex]a=1[/tex], [tex]b=-9[/tex], and [tex]c=-20[/tex]
then, replacing these values in the formula, we obtain:
[tex]x=\frac{-b+/-\sqrt{b^2-4\,a\,c} }{2\,a}\\x=\frac{-(-9)+/-\sqrt{(-9)^2-4\,(1)\,(-20)} }{2\,(1)}\\x=\frac{9+/-\sqrt{(-9)^2-4\,(1)\,(-20)} }{2\,(1)}[/tex]
Which looks like the third expression you are listing (although it is a little hard to read)